ATAD2 overexpression is associated with progression and prognosis in colorectal cancer. (26th January 2016) - Hou, Mingming; Huang, Rui; Song, Yanni; Feng, Di; Jiang, Yang; Liu, Ming
Abstract: Objectives: ATPase family AAA domain-containing 2 plays an important role in tumor progression including cell cycle, proliferation, apoptosis and chemoresistance. However, the expression of ATPase family AAA domain-containing 2 in colorectal cancer and its significance are still unclear. The aim of this study was to examine the expression of ATPase family AAA domain-containing 2 in colorectal cancer. Methods: Immunohistochemistry was used to determine the expression of ATPase family AAA domain-containing 2 in 155 colorectal cancer and 30 matched adjacent noncancerous tissues. The correlation of ATPase family AAA domain-containing 2 expression with clinicopathological variables was assessed using chi-square test. Patient survival was analyzed using the Kaplan–Meier and log-rank tests. Cox regression was performed for the multivariate analysis of prognostic factors. Results: High expression of ATPase family AAA domain-containing 2 was detected in 58.1% of the colorectal cancers and was significantly associated with advanced tumor-node-metastasis stage ( P = 0.044), poor differentiation ( P = 0.028), deep infiltration ( P < 0.001), lymphovascular invasion ( P = 0.006), lymph node metastasis ( P = 0.024) and recurrence ( P = 0.022). Patients with high ATPase family AAA domain-containing 2 expression had significantly poorer overall survival and disease-free survival (both P < 0.001) when compared with patients with low expression of ATPase family AAA domain-containing 2. The multivariate analysis showed that ATPase family AAA domain-containing 2 was an independent factor for both overall survival ( P = 0.003; hazard ratio (HR): 2.356; 95% confidence interval (CI): 1.335–4.158) and disease-free survival ( P = 0.001; HR: 2.643; 95% CI: 1.489–4.693). Conclusions: These results showed that ATPase family AAA domain-containing 2 overexpression was associated with progression and prognosis of colorectal cancer.